Pendayagunaan Zakat Produktif Dompet Dhuafa Yogyakarta dalam Perspektif Maqasid Syari'ah - Fahmi Irfanudin (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2019)
One of the main objectives of the zakat is to improve the welfare of the mustahiq. In order for this to be realized, it is necessary to choose the right empowerment program, accompanied by a mustahiq assistance process that is sustainable and well managed by the 'zakat institution. This is where the importance of zakat utilization programs that are productive.This study aims to uncover and explain the productive zakat, the model of productive zakat utilization in Dompet Dhuafa Yogyakarta, and the model of utilizing productive zakat in Dompet Dhuafa Yogyakarta in the perspective of Maqāṣid al-Sharī`ah.This research is a field research and literature that collects qualitative data with sociological and normative approaches. This research is descriptive, that is by describing problems which are then analyzed in depth. Data collection is generally carried out by searching on written sources, as well as field sources in the form of data obtained through documentary studies, as well as observations and interviews to strengthen research results.The results of this study indicate that the Dompet Dhuafa Yogyakarta productive zakat program is able to realize benefits and improve the welfare of the mustahiq.Of course, this is in accordance with the main objectives of the Sharī`ah (Maqāṣid al-Sharī`ah) which is to realize human welfare which lies in the protection of religion (ad-dīn), soul (an-nafs), reason (al-'ql), descent (an- nasl), and their wealth (al-māl).